2012
DOI: 10.4103/0971-4065.83741
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in a renal allograft recipient presenting with intussusception

Abstract: Extra-pulmonary tuberculosis (TB) is more common in renal allograft recipients and may present with dissemination or an atypical features. We report a renal allograft recipient with intestinal TB presenting 3 years after transplantation with persistent fever, weight loss, diarrhea, abdominal pain and mass in the abdomen with intestinal obstruction. He was diagnosed to be having an ileocolic intussusception which on resection showed a granulomatous inflammation with presence of acid-fast bacilli (AFB) typical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…10-20% of patients present with pyrexia of unknown origin [29]. Organ involvement is similar to that seen in general population, though rare manifestations (such as intussusception) are possible [32].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 71%
“…10-20% of patients present with pyrexia of unknown origin [29]. Organ involvement is similar to that seen in general population, though rare manifestations (such as intussusception) are possible [32].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 71%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
“…IRIS has recently been described with increasing frequency in SOT recipients who are undergoing treatment for TB and other opportunistic infections who have necessarily had to have their immunosuppression curtailed [ 9 , 10 , 14 ]. Review of the literature documenting IRIS in SOT has revealed 3 case reports and 1 retrospective study documenting 9 cases, which include 6 liver, 4 kidney, 1 heart, and 1 heart lung transplant [ 10 , 14 16 ].…”
Section: Discussionmentioning
confidence: 99%